Cholesterol-lowering effects of oat β-glucan: a meta-analysis of randomized controlled trials - Whitehead, Anne; Beck, Eleanor J; Tosh, Susan; Wolever, Thomas MS (The American journal of clinical nutrition, 2014)
Background: Health claims regarding the cholesterol-lowering effect of soluble fiber from oat products, approved by food standards agencies worldwide, are based on a diet containing ≥3 g/d of oat β-glucan (OBG). Given the number of recently published randomized controlled trials (RCTs), it is important to update the findings of previous meta-analyses.Objective: The objective was to quantify the effect of ≥3 g OBG/d on serum cholesterol concentrations in humans and investigate potential effect modifiers.Design: A meta-analysis was performed on 28 RCTs comparing ≥3 g OBG/d with an appropriate control. Systematic searches were undertaken in PubMed, AGRICOLA, and Scopus between 1 January 1966 and 6 June 2013, plus in-house study reports at CreaNutrition AG. Studies were assessed with regard to inclusion/exclusion criteria, and data were extracted from included studies by reviewers working independently in pairs, reconciling differences by consensus. Estimates of the mean reduction in serum cholesterol from baseline between the OBG and control diets were analyzed by using random-effects meta-analysis models and meta-regression.Results: OBG in doses of ≥3 g/d reduced low-density lipoprotein (LDL) and total cholesterol relative to control by 0.25 mmol/L (95% CI: 0.20, 0.30; P < 0.0001) and 0.30 mmol/L (95% CI: 0.24, 0.35; P < 0.0001), respectively, with some indication of heterogeneity (P = 0.13 and P = 0.067). There was no significant effect of OBG on high-density lipoprotein (HDL) cholesterol or triglycerides and no evidence that dose (range across trials: 3.0–12.4 g/d) or duration of treatment (range: 2–12 wk) influenced the results. LDL cholesterol lowering was significantly greater with higher baseline LDL cholesterol. There was a significantly greater effect for both LDL and total cholesterol in subjects with diabetes compared with those without (although based on few studies).Conclusions: Adding ≥3 g OBG/d to the diet reduces LDL and total cholesterol by 0.25 mmol/L and 0.30 mmol/L, respectively, without changing HDL cholesterol or triglycerides.